REPRESENTASI PRAKTEK PERBUDAKAN DAN PENINDASAN DALAM PUISI "˜NEGRO' KARYA LANGSTON HUGHES: SEBUAH KAJIAN POSKOLONIAL - Amalia, Ila (Diksi, 2021)
(Title: Representation of Slavery and Oppression Practices in 'Negro' Poetry by Langston Hughes: A Postcolonial Study). This study aims to describe the forms of oppression and slavery practices caused by racial discrimination and colonialism practices. With a background of slavery experienced by blacks in this case the African nation, the analysis of this poem aims to see how: (1) The form of slavery and oppression carried out by the colonials against the colonized people depicted in the poem "Negro" by Langston Hughes, (2) Forms of struggle and response carried out by colonized nations towards the practice of oppression illustrated in the poem "Negro" by Langston Hughes. The postcolonial theory approach is used as a foundation in the analysis of the poetry. The data source is taken from a poem by Langston Hughes with the theme of discrimination and racial subordination of African-Americans entitled "Negro" written in 1922. The results show that black people have experienced oppression in the form of slavery, forced/hard workers, victims of cruelty, and art workers who express their stories and historical experiences through their songs. One of the efforts made by colonized nations to fight against colonial practices is through civil movements, including through literary works. Later this civil movement led to the discourse of the abolition of slavery throughout the world.Keywords: postcolinial, colonialism, oppression, slavery, Africa